PENERAPAN PERENCANAAN PAJAK PENGHASILAN BADAN PADA CV X DI SIDOARJO - Nurrokhmat, Andi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
This research is meant to analyze the implementation of tax planning which is conducted by CV X with tax regulation. Tax is a compulsory contribution to the country which is owed by personals or entities which are forced by the legislation, by having no direct reward and it is entirely used for government needs to provide prosperity for the people. Tax, actually, can be managed and controlled by comprehending the prevailing tax regulation and its development correctly and by following its changes so the efficiency of tax payment can be achieved. Qualitative descriptive method and case study method are applied in this research. The description of the research object is companyâs income tax which is imposed to the CV X by using the companyâs profit and loss income statement in order to perform fiscal correction. So it will generate fiscal financial and profit fiscal report which will be used to arrange tax planning and it will be compared to the profit before and after tax planning. The result of the research indicates that the tax planning is implemented, tax which should be paid by the CV X is as much as Rp 293.146.003 while after the tax planning the tax which should be paid by the CV X is as much as Rp 285.124.838 in 2011. The tax which should be paid by CV X can be optimized by carrying out tax planning. Keywords: Tax Planning, Fiscal Correction, Tax Regulation, Owed Tax